New world maker radical poetics, Black internationalism and the translations of Langston Hughes - Kernan, Ryan James 1975- (Northwestern University Press, 2022)
"New World Maker reappraises Langston Hughes's political poetry, reading the writer's leftist works in the context of his practice of translation to reveal an important meditation on diaspora"--
Keywords: Hughes, Langston -- 1902-1967; Literatur; Lyrik; Übersetzung; Hughes, Langston / 1902-1967 / Criticism and interpretation; Poetry / Translating; Poetry / Black authors / History and criticism; Poésie / Auteurs noirs / Histoire et critique; Hughes, Langston / 1902-1967; Poetry / Black authors; Criticism, interpretation, etc